دراسة مقارنة في حساب ثبات عدد من الاختبارات البدنية بين طريقتي الصور المتكافئة وتطبيق الاختبار واعادة تطبيقه - حسين, مؤيد; نذير, محمد; مطلك, سليمان (جامعة الوادي - University of Eloued, 2022)
ملخص البحث أهمية البحث الحالي في التعرف على الفروقات الإحصائية بين حساب ثبات بعض الاختبارات البدنية بطريقتي اعادة الاختبار والصور المتكافئة بأعتبارهما اكثر طرق استخراج الثبات. مشكلة البحث لدى الباحثون في عدم التزام الباحثين بطريقة محددة في احتساب الثبات في جميع البحوث مما ادى الى وجود اختلاف في نتائج حساب الثبات بطريقتي تطبيق الاختبار واعادة تطبيقه والصور المتكافئة، لذا ارتاى الباحثون دراسة هذه المشكلة للتعرف على الفروقات الاحصائية بين هذين الطريقتين في احتساب الثبات ومن ثم تحديد الطريقة الانسب منهما والاصح في احتساب الثبات للاختبارات المدروسة في البحث. يهدف البحث الحالي الى: - الفروقات الاحصائية بين درجات الثبات بطريقتي اعادة الاختبار والصور المتكافئة لعدد من الاختبارات البدنية. ويفترض الباحثون: - وجود فروقات ذات دلالة احصائية بين درجة الثبات بطريقتي اعادة الاختبار والصور المتكافئة لعدد من الاختبارات البدنية. واستنتج الباحثون: - تفوق طريقة تطبيق الاختبار واعادة تطبيقه على طريقة الصور المتكافئة في احتساب الثبات للاختبارات البدنية اللاهوائية القصيرة لعينة البحث. A comparative study in calculating the stability of a number of physical tests between the two methods of equivalent images and the application and re-application of the test - Research Summary - The importance of the current research in identifying the statistical differences between calculating the stability of some physical tests in the two methods of retesting and equivalent images, as they are the most methods of extracting stability used in the field of physical education research. - The research problem appeared among the researchers in the researchers’ lack of commitment to a specific method in calculating stability in all research, which led to a difference in the results of calculating stability in the two ways of applying the test and re-applying it and equivalent images, so the researchers decided to study this problem to identify the statistical differences between these two methods in calculating stability. And then determine the most appropriate and correct method of calculating the stability of the tests studied in the research. - The method of applying and re-applying the test is superior to the stoichiometric method in calculating the stability of the short anaerobic physical tests of the research sample.
مقال
Keywords: ثبات الاختبارات ، إعادة الاختبار ، الصور المتكافئة